(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The article takes its inspiration from the tragic events of Cutro and Pylos in Greece and it is aimed to highlight the dramatic nature of the immigration crisis. As it is widely known, the migration phenomenon mainly develops along the central Mediterranean and the Balkans route, and it has undoubtedly made worst by the war in Ukraine. The analysis of the European and domestic legal framework, which justifies the summa divisio between refugees and ‘mere’ migrants, is conducted in order to emphasise the existence of a legal migrants’ status very often at odd with the security demands of each single state. Furthermore, the control of the migratory phenomenon is worsened by the stratification of a plurality of legislative approaches which have favoured, on several occasions, the development of a disorganised discipline, resulting in interpretational and enforcement difficulties. Not infrequently, the issue of balancing conflicting interests takes on dramatic tones. This is the case with the immigrant’s right to health, constantly challenged by the limits arising from the public finance, due to the costs for implementing the so called “social rights”.